DIEP flap salvage by cannula venesection of the superficial inferior epigastric vein - Wongtriratanachai P. (2017)
© 2016, The Author(s). The deep inferior epigastric perforator (DIEP) flap is a technique of autologous breast reconstruction that is gaining popularity. The main advantage of the DIEP flap over the traditional transverse rectus abdominis myocutaneous (TRAM) flap is that there is a lower incidence of abdominal wall donor-site morbidity with the DIEP flap. However, venous congestion is the most dreaded complication of DIEP flap surgery which requires prompt intervention. In this case report, we present a simple but effective procedure to salvage the congested DIEP flap. A 55-year-old female underwent left breast reconstruction with DIEP flap and developed venous congestion during surgery. Cannula venesection of the superficial inferior epigastric vein (SIEV) was performed intraoperatively followed by intermittent aspiration of blood for 3 days. A satisfactory aesthetic result was achieved with no evidence of fat necrosis. This procedure eliminated the need for performing an additional microvascular anastomosis, required less operative time, and allowed augmentation of the venous drainage of the congested flap. Level of Evidence: Level V, therapeutic study.